Effect of molecular weight on the properties of liquid epoxidised natural rubber acrylate (Lenra )/silica hybrid composites - Eda Yuhana Ariffin,; Azizan Ahmad,; Dahlan Hj Mohd,; Mahathir Mohamed, (Universiti Kebangsaan Malaysia, 2011)
This paper reports on the effect of molecular weight on the morphological and mechanical properties of liquid epoxidised natural rubber acrylate (LENRA)/silica hybrid composites prepared by sol-gel technique. The sol-gel reaction was conducted at different concentration of tetraethylorthosilicate (TEOS), used as a precursor of silica. TEOS were introduced in 10, 20, 30, 40 and 50 parts per hundred rubber (phr) in the composites. Two different molecular weights of ENR were used to study the effect of molecular weight on the mechanical and morphological properties of the compounds. These compounds were cured by ultraviolet (UV) irradiation. The mechanical properties were studied through pendulum hardness and scratch tests. Higher molecular weight of ENR showed better mechanical properties than lower molecular weight. Transmission electron microscope was used to determine the silica size and to study the distribution and dispersion of the silica particles. High molecular weight showed greater distribution and dispersion of silica particles with diameter of 13 nm–256 nm. Morphological and mechanical properties of LENRA/silica hybrid composites were improved by using high molecular weight of ENR